The test of marine aerosol sampling aboard the research vessel "SHIRASE" (abstract) - Nishikawa, Masataka; Mizoguchi, Tsuguo; Kanamori, Satoru; Kanamori, Nobuko; Aoki, Syuji (National Institute of Polar Research, 1989)
P(論文) The research vessel "SHIRASE" was used for test sailing from Tateyama in Chiba prefecture to Nagoya via Miyake Island in September 1987. Marine aerosols were measured aboard every hour by departmental bulletin paper